Social media advertisements and their influence on consumer purchase intention - K. V. Sriram; K. P. Namitha; Giridhar B. Kamath (Cogent Business & Management, 2021)
Rapid rise in social media users has spawned a new form of advertising for businesses called social media advertising. Advertisers have long faced one of the most important challenges: low consumer acceptability of commercials. It is vital to identify the most salient elements of social media advertisements that influence how consumers see them. The purpose of this study is to determine the factors that influence how social media advertisements are perceived and their effect on customer purchase intent. We performed a survey and utilized exploratory factor analysis to determine which characteristics significantly influenced how people perceived social media advertisements. Structural Equation Modelling was used to investigate the effect of customer characteristics on purchase intention. The findings indicate that creative characteristics, attention-grabbing details, emotional appeal, and celebrity endorsement all had an effect on how social media advertising was evaluated. The study discovered that elements such as attention-grabbing details, celebrity endorsement, and emotional appeal have a considerable impact on customer purchase intention. A sufficient emphasis on the aforementioned traits would aid in the development of effective social media marketing and increase consumer buying intent.
Keywords: 650; Social media advertisements; perception; consumer purchase intention; creative characteristics; emotional appeal; celebrity endorsement